Homozygous duplication identified by whole genome sequencing causes LRBA deficiency - Daniele Merico (Nature Portfolio, 2021)
Abstract In more than one-third of primary immunodeficiency (PID) patients, extensive genetic analysis including whole-exome sequencing (WES) fails to identify the genetic defect. Whole-genome sequencing (WGS) is able to detect variants missed by other genomics platforms, enabling the molecular diagnosis of otherwise unresolved cases. Here, we report two siblings, offspring of consanguineous parents, who experienced similar severe events encompassing early onset of colitis, lymphoproliferation, and hypogammaglobulinemia, typical of lipopolysaccharide-responsive and beige-like anchor (LRBA) or cytotoxic T lymphocyte antigen 4 (CTLA4) deficiencies. Gene-panel sequencing, comparative genomic hybridization (CGH) array, and WES failed to reveal a genetic aberration in relevant genes. WGS of these patients detected a 12.3 kb homozygous tandem duplication that was absent in control cohorts and is predicted to disrupt the reading frame of the LRBA gene. The variant was validated by PCR and Sanger sequencing, demonstrating the presence of the junction between the reference and the tandem-duplicated sequence. Droplet digital PCR (ddPCR) further confirmed the copy number in the unaffected parents (CN = 3, heterozygous) and affected siblings (CN = 4, homozygous), confirming the expected segregation pattern. In cases of suspected inherited immunodeficiency, WGS may reveal a mutation when other methods such as microarray and WES analysis failed to detect an aberration.